Community perceptions of the social and economic impacts of COVID-19 in Myanmar: Insights from round 4 of the National COVID-19 Community Survey (NCCS) – October 2020 - Oo, Than Zaw; Lambrecht, Isabel B.; Headey, Derek D.; Goudet, Sophie (International Food Policy Research Institute, 2020)
To continue monitoring the economic and social impacts of the COVID-19 crisis on Myanmar’s diverse rural and urban communities, a multi-round large-scale community telephone survey is being conducted. This report focuses on key findings from the fourth round of the survey conducted in October 2020. This survey round obtained information from community respondents that had participated in the June/July, August, and September rounds, as well as from additional communities. In total, the fourth round obtained responses from 190 townships across Myanmar: 57 from the Dry Zone, 67 from the Delta, 19 from Southeast Myanmar, 35 from North Myanmar, and 12 from West Myanmar.